HABITAT SUITABILITY SPATIAL MODEL OF NEAR THREATENED SUNDA TEAL ANAS GIBBERIFRONS (MULLER, 1842) (ANSERIFORMES: ANATIDAE) IN MUARA ANGKE WETLANDS, JAKARTA, INDONESIA - Andri Wibowo; Adi Basukriadi; Erwin Nurdin; Nana Suryana Nasution (BRIN Publishing (Penerbit BRIN), 2022)
Wetland ecosystems are important habitats for many waterbird species, including the IUCN nearthreatened Sunda Teal Anas gibberifrons, a species that inhabit wetlands in Indonesia. Muara Angke is one of few remaining wetlands located in Jakarta and has potential as an important habitat for Sunda Teal. This study aims to assess and model suitable habitat for near-threatened Sunda Teal in remaining wetlands in Muara Angke in Jakarta, Indonesia. The study areas include an ecotourism park, the western and eastern parts of the Angke protected forest, and the wildlife reserve. Remote sensing data and geographic information system (GIS) analysis were employed to assess Sunda Teal’s habitat suitability. Some environmental variables negatively influencing habitat suitability for the species include the presence of fishponds and settlements, and represent anthropogenic disturbance. In contrast, variables that may positively influence the species include the occurrence of gastropod and crustacea, both groups being known as food resources, and mangrove cover. The highly and moderately suitable habitats were estimated to form 32.36% and 23.48% of the total wetlands, respectively. In contrast, 12.17% was considered unsuitable for Sunda Teal. The ecotourism park had the most unsuitable habitats. In contrast to the ecotourism park, the protected forest, followed by the wildlife reserve, had more moderately and highly suitable habitats.